FACTORAL STRUCTURE OF RESISTANCE TO COMBAT PSYCHOLOGICAL TRAUMATIZATION AT SUSTAINABLE TYPE OF LAW ENFORCEMENT AGENTS WITH DIFFERENT LEVEL OF TRAFFIC EXPERIENCE - Kolesnychenko, Oleksandr (PSYCHOLOGICAL JOURNAL, 2019)
The article reveals the results of an empirical study of the factor structure of resistance to combat psychological trauma among the law enforcement officers of a stable type with a different level of trauma of combat experience. Dedicated six factorial structure of resistance to combat psychological trauma among law enforcement officers of a downward type with a low level of traumatic experience of combat: the first factor is indicated as: “Viability as an active position of relative control of a dangerous situation"; the second factor is indicated as: “Internality as readiness to work to overcome difficulties as readiness for risk-taking activities "; the third factor is designated as “Police officer’s professional knowledge”; the fourth factor is so “Awareness of the settlement of professional activities”; the fifth factor was designated as “Professional (non-emotional) courage”; The sixth factor is designated as “Syncreticity of coping strategies”. For law enforcement officers of a descending type with an average level of traumatic experience of combat experience, the six factorial structure of resistance to combat psychological traumatization is as follows: the first factor is “Differentiated internality of professional activity in a dangerous situation”; the second factor “Coping as active control of a dangerous situation”; the third factor is “Coping as an experience of a dangerous situation”; the fourth factor is “Professional independence”; the fifth factor is “The ability to independently decide on the need to avoid the inactive professional action algorithm”; The sixth factor is “Unstoppable courage”. The structure of resistance to trauma among law enforcement officers of a descending type with a high (acquired) level of trauma of combat experience combines both the poles of its development: the first factor is “Holistic internality”; the second factor is “Team Professionalism”; the third factor “Conscious attitude to the normative regulation of the professional activity and communication of law enforcement officers”; the fourth factor is “Objectivity of perception of the situation and its place in it”; the fifth factor is “Acquisition of a professional algorithm of actions in combat conditions, adaptation to them”; The sixth factor is “Acquisition of personal maturity, wisdom”. It was established that the law enforcement officers of the descending type with the accumulation of combat experience, resistance to combat mental trauma during the first stages of entering a combat situation is largely determined by the learned experience of the actions of their professional group. Learned experience allows them to develop their own style of interaction with a traumatic combat situation, followed by an awareness of the strengths and weaknesses of the experiences of others.